GAMING TECHNOLOGY IN ENGLISH LESSONS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article discusses the theoretical implications of using gaming technology in English classes at a comprehensive school and classifies games according to their didactic orientation and form. The author examines this technology briefly from a psychological perspective, focusing on the efficacy and pedagogical viability of using the game at various stages of the lessons. The article, for example, provides an adversarial team game for memorizing words that can be used to learn any subject and help students improve their vocabulary.